Multisystem Inflammatory Syndrome in Children (MIS-C) Following SARS-CoV-2 Infection: Role of Oxidative Stress - Graciano-Machuca, Omar; Villegas-Rivera, Geannyne; López-Pérez, Iván; Macías-Barragán, José; Sifuentes-Franco, Sonia (Frontiers in Immunology, 2021)
With the appearance of the SARS-CoV-2 virus in December 2019, all countries in the world have implemented different strategies to prevent its spread and to intensively search for effective treatments. However, understanding the molecular mechanisms involved in its pathophysiology is an important challenge. Recently, the severe disease of COVID-19 has been associated with an excessive amount of pro-inflammatory cytokines and an increase in reactive oxygen species. Initially, severe cases of the disease were considered in adult patients; however, cases of older school-age children and adolescents who presented fever, hypotension, severe abdominal pain and cardiac dysfunction, positive for SARS-CoV-2 infection, have been reported, with increased pro-inflammatory cytokines and tissue damage. Understanding the pathophysiological mechanisms of oxidative stress and inflammation and their association with multisystemic inflammatory syndrome in children with SARS-CoV-2 infection is important to help explain the clinical characteristics observed in these patients. The aim is to review the pathophysiology of SARS-CoV-2 and its relationship with oxidative stress and the consequent increase in inflammation in multisystemic inflammatory syndrome in children.